Caught in the Crossfire: Doctors’ Battle with Emotional Strain and Resource Shortages (Lesson Learned from Covid-19 Pandemic) - Lestari, Diyah Woro Dwi; Hidayah, Arfi Nurul; Ferine, Miko; Wicaksono, Raditya Bagas; Dinata, Ageng Bella; Muhaimin, Amalia; Octavilia, Ernasiwi Astri; Maghfiroh, Nisaul; Kamal, Isran (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Healthcare professionals, particularly doctors, navigate a delicate balance between empathy and emotional resilience, a challenge that became more pronounced during the COVID-19 pandemic. This study explores the experiences of doctors in managing empathy while coping with burnout, compassion fatigue, and resource scarcity. Through in-depth interviews with general practitioners and specialists, four key themes emerged: the emotional impact of patient conditions on doctors, the heightened burnout caused by excessive workloads, the distress of resource shortages, and the struggle to maintain professionalism despite emotional strain. Findings highlight the dual nature of empathy—while essential for patient care, it also contributes to emotional exhaustion. The study underscores the urgent need for systemic support, including psychological interventions and institutional strategies, to sustain healthcare professionals' well-being and ensure compassionate yet sustainable medical practice.